2021
DOI: 10.1177/19458924211021031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sinonasal Histopathological Changes in Biological Treatment of Eosinophilic Chronic Rhinosinusitis

Abstract: Background Biologic therapies such as mepolizumab and benralizumab are currently utilised in the treatment of eosinophilic asthma, and are emerging in the management of eosinophilic chronic rhinosinusitis (eCRS). These biologics inhibit the interaction of IL-5 with its receptor, thus impairing cytokine signalling and eosinophil inflammation. Mepolizumab does so by targeting IL-5, whereas benralizumab targets the α chain of the IL-5 receptor. This study compares the sinonasal tissue response to anti-IL-5 biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In the absence of a universally acceptable standardized tissue eosinophil cut-off count, 10 we used 10/hpf as it is one of the most widely described criteria in published literature. [11][12][13][14][15] Soler et al 16 used absolute tissue eosinophil counts until they defined the cut-off point with the largest absolute difference in disease-specific quality of life scores and smallest p-value, which was identified at ≥10 eos/hpf. However, few transcriptomic studies have compared eCRS and neCRS, [17][18][19][20][21][22][23] and these studies have been based on Asian populations only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a universally acceptable standardized tissue eosinophil cut-off count, 10 we used 10/hpf as it is one of the most widely described criteria in published literature. [11][12][13][14][15] Soler et al 16 used absolute tissue eosinophil counts until they defined the cut-off point with the largest absolute difference in disease-specific quality of life scores and smallest p-value, which was identified at ≥10 eos/hpf. However, few transcriptomic studies have compared eCRS and neCRS, [17][18][19][20][21][22][23] and these studies have been based on Asian populations only.…”
Section: Discussionmentioning
confidence: 99%
“…We studied the transcriptomic signatures of CRS based on its phenotype (CRSwNP and CRSsNP) and endotype (<10 eos/hpf and > 10 eos/hpf) by whole tissue RNA‐Seq. In the absence of a universally acceptable standardized tissue eosinophil cut‐off count, 10 we used 10/hpf as it is one of the most widely described criteria in published literature 11–15 . Soler et al 16 used absolute tissue eosinophil counts until they defined the cut‐off point with the largest absolute difference in disease‐specific quality of life scores and smallest p ‐value, which was identified at ≥10 eos/hpf.…”
Section: Discussionmentioning
confidence: 99%
“…3 Ho et al demonstrated that sinonasal tissue of patients with eosinophilic chronic rhinosinusitis (eCRS) treated with mepolizumab had predominately eosinophilic inflammation despite biologic therapy and more severe subepithelial edema while patients treated with benralizumab had predominate lymphoplasmacytic inflammation. 14 No study to date has identified histopathologic changes produced by dupilumab. The purpose of this study is to determine the histopathologic features in patients with CRSwNP who underwent FESS following failure of biologic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Representative studies using prospective and/or retrospective data have previously confirmed the higher rate of responders compared with those of super responders. 4,5 One possible limitation is the fact that only those patients who continue with mepolizumab are analyzed at 24 months, leading to a "selection-bias", because patients who continue therapy are presumably those who experience greater improvement.…”
mentioning
confidence: 99%